Interactive Documentary: The Awareness of Music As Stress Reliever - Ahmad Muzambique Arjuana; Jessifa Joanna Mohd Supian (Journal of Computing Technologies and Creative Content, 2022)
This project focuses on the issue of mental pressure experienced by Final Year undergraduate students. Specifically, this research was led to distinguish the relationship of mental pressure with music treatment. In addition, the project to analyze methods that can be utilized by students to address the mental pressure they experienced. The project’s data was collected through interviews and survey. A sum of 30 final year students comprising of 25 male and 25 females participated in the survey. The research instruments were used to quantify the adequacy of music treatment in managing pressure among the students. The ADDIE model is the instructional design model that has been used in this study. Based on the result, 90% of respondents strongly agree that music can be a stress reliever. It is hoped that the outcomes can help address the issue of mental pressure experienced by the students.